Development and recovery : the realities of the new interdependence : report - United Nations Conference on Trade and Development; Corea, Gamani (New York : United Nations, 1984)
This is a report of the UNCTAD VI conference. The central theme of the conference was the need for action both to stimulate recovery in the industrialized countries and to reactivate development in the developing countries as processes that reinforce each other.
"Gamani Corea, Secretary-General of UNCTAD"--P. iii.
"TD/271/Rev.1"--Cover.
"United Nations publication sales no. E.84.II.D.4"--T.p. verso.
Includes bibliographical references.
osc 09/01/2019
Loans
Keywords: Economic development; International economic relations; Economic history